Agrarian Revolution: A Viable Model for Nepal’s Development - Bhandari, Bishnu B. (NCWA Annual Journal, 2025)
Nepal is an agrarian country. Its economy is based on land and agricultural activities. The total population that depends on agriculture for livelihood is about 67%. About 20.27% of the population is below the absolute poverty line. The data on Gross Domestic Product (GDP), poverty, rice production, productivity and import indicate that the present models, plans and strategies of agricultural development have not been effective in reaching out to the targeted group of farmers to improve their livelihood and lifestyle. Rice productivity and production have increased slightly but not the area under its cultivation. The condition of farmers is downtrodden and deteriorating. Land distribution and land tenure systems are defective. So, the present models of agricultural development are not working well. Therefore, we need to make a paradigm shift for which we need to take a common resource into consideration that is directly connected to a large population of farmers who are dependent on their survival on farmland. This article proposes an agrarian revolution in Nepal where it focuses on the simultaneous betterment of farmland, farmers and farming in a balanced way. The revolution envisions the development of land use plans, equitable land distribution, social welfare of farmers and the use of technology in farming. It further concludes that for the agrarian revolution to be successful, it needs all-out support of the government, active and responsible participation of farmers, political will and determination of the leaders and policymakers. In sum, the agricultural revolution is the foundation for making Nepal a strong and prosperous country.